Functional improvement of unicompartmental knee arthroplasty compared with total knee arthroplasty for subchondral insufficiency fracture of the knee - Dae Keun Suh; Jun-Gu Park; Jaejoong Kim; Dong Won Suh; Seung-Beom Han (Scientific Reports, 2023)
Abstract Subchondral insufficiency fracture of the knee (SIFK) causes acute knee pain in adults and often requires surgical management. Unicompartmental knee arthroplasty (UKA) and total knee arthroplasty (TKA) are the two most common surgical treatments for SIFK. While both UKA and TKA have their advantages, there is no consensus for SIFK localized on the medial compartment. We hypothesized that patients with SIFK treated with UKA would show superior patient-reported outcomes compared to those who underwent TKA. A total of 90 patients with SIFK located medially were included in the TKA (n = 45) and UKA (n = 45) groups. Size of SIFK lesions were measured on MR images. Patient reported outcomes in the form of the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Hospital Special Surgery (HSS) scores, and Knee Society Scores (KSS) were assessed preoperatively, postoperative 6, 12 months, and at the final follow-up. There were no differences in the size of the SIFK lesion between two groups. At 6 months, WOMAC score was better in the UKA group than the TKA group (p < .01). Both groups had a significant improvement in WOMAC, HSS, and KSS scores at the final follow-up compared to preoperative scores. The UKA group had better range of motion of the knee preoperatively and postoperatively than the TKA group (p < .01 and p < .01). UKA group showed a higher relative risk than the TKA group in terms of complications (RR = 3.0) but with no statistical significance (P = 0.31). Unicompartmental arthroplasty and total joint arthroplasty can produce successful outcomes in patients with SIFK with proper patient selection, regardless of the size of SIFK lesion.